Using a collaborative zine to co-produce knowledge about location-based virtual reality experiences. (1st July 2021) - Nash, Richard; Yamada-Rice, Dylan; Dare, Eleanor; Love, Steve; Main, Angus; Potter, John; Rodrigues, Deborah
Abstract : Purpose: The purpose of this paper is to focus on a designed research methodology to distil existing research findings from an esrc/ahrc funded japan/uk network on location-based virtual reality experiences for children in order to generate new knowledge. Design/methodology/approach: The structured co-production methodology was undertaken in three stages. These were: (1) a collaborative workshop which produced a series of collage narratives, (2) collaborating with a non-human entity in the form of a digital coded tool to reconfigure the workshop responses and mediate the hierarchy of roles, (3) the co-production of a zine as a collaborative reflection method, which shared via postal service enabled a dialogue and exchange of round Robin interventions by the network members. Findings: The analysis of the data collected in this study highlighted five themes that could be used by other researchers on a wide range of projects. These were: (1) knowing through making, (2) the importance of process, (3) beyond linear representations, (4) agency of physical materials and (5) agency of digital code. Research limitations/implications: The context of the study being undertaken during the first phase of the global pandemic, revealed insight into a method of co-production that was undertaken under emergency remote working conditions. The knowledge generated from this can be applied to other research contexts such as working with researchers or participants across global borders without the need to travel. Originality/value: The research provides an innovative rethinking of co-production methods in order to generate new knowledge from multidisciplinary and multimodal research.